2007
DOI: 10.1080/00016480600740589
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of a multidisciplinary tumour meeting for patients with head and neck cancer

Abstract: Head and neck oncology MDT meetings are held in our region to establish a correct diagnosis and an appropriate treatment plan for each reviewed patient. The quality of these MDT meetings was assessed based on the following factors: How often can a diagnosis, a TNM-classification and a treatment plan be successfully established from the workup presented at the patient's first MDT meeting? And what are the reasons for failure? Further, how often are the TNM-classification altered at treatment start? All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 20 publications
2
43
1
Order By: Relevance
“…Our finding that a decision could be reached in 85 % of cases is in line with previous findings from studies performed in France and Sweden. 19,20 The authors of a previous study also found that failure of decision-making was related to inadequate information on imaging, staging, histology, and comorbidities, which is consistent with our own analysis. 20 The findings of this study have several implications for MDT working.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that a decision could be reached in 85 % of cases is in line with previous findings from studies performed in France and Sweden. 19,20 The authors of a previous study also found that failure of decision-making was related to inadequate information on imaging, staging, histology, and comorbidities, which is consistent with our own analysis. 20 The findings of this study have several implications for MDT working.…”
Section: Discussionsupporting
confidence: 91%
“…7 Existing studies have suggested that the ability of a MDT to reach a treatment decision for any given case, along with measures of the quality of information and teamwork, can be useful markers of team performance. 19,20 To date, however, no studies have prospectively and scientifically assessed the effect of factors, such as the quality of available information, teamworking, or timing of meetings, on the ability of the MDT to make clinical decisions.…”
mentioning
confidence: 99%
“…The reconfiguration of cancer services following recommendation for MDT working [4] is attributed, at least in part, to an increase in staff stress [23]. Patients clearly benefit from being treated by a surgeon with a high workload [24], but the impact of the stress and emotional exhaustion identified in MDTs [25] has yet to be measured, and [26] suggests that quality assurance measures are needed. While several have sought to identify the factors that help MDTMs work better [27][28][29] a general formula for success remains elusive.…”
Section: Analysis Of the Effects Of Mdtmsmentioning
confidence: 99%
“…12,13 Failure of the team to consider all relevant information may lead to poor decisions, or to decisions which are not implemented as they are unacceptable to patients or clinically inappropriate. [14][15][16][17] Nonimplementation of MDT meeting recommendations can have both clinical and financial consequences if further discussion is required and treatment is delayed.…”
mentioning
confidence: 98%